A Child's Garden Of Verses - "Louis, Robert" (Puffin books, 1994)
Poems about childhood, capturing a child's wonder, imagination, and fascination with everyday things. From the make-believe world of "The land of the counterpane" to the simple pleasure of "At the seaside", the curiosity of "Auntie's skirts" to the dreams of "Foreign lands". Grades 2-4. 1992
Keywords: Children's poetry